Penerapan Model Pembelajaran Problem Possing untuk Meningkatkan Hasil Belajar Siswa Kelas VII SMP Sabiluttaibin - Azizah, Nur; Irawati, Tri Novita (FKIP Universitas Islam Jember, 2021)
This research has a purpose to improve student learning outcomes in studying integers using the application of the Problem Possing learning model. The type of research used is Classroom Action Assessment (PTK), with research procedures using a cycle model, from the results of the study the percentage of student learning outcomes in cycle I reached 60% and cycle II was 90%. This proves that the level of understanding of students increases with the application of the Problem Possing learning model, so that learning can provide an overview with examples of basic illustrations.